The Use of The Duolingo Application in Improving Students’ Vocabulary Mastery to the Eleventh-Grade Students of SMK Gemilang Modernland in the Academic Year 2023/2024 - Rihana, Athiya Luthfiana; Ramalia, Tenia; Kurniawan, Andri (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2024)
This research was conducted to investigate the use of the Duolingo application in improving students’ vocabulary mastery to the eleventh-grade students of SMK Gemilang Modernland in the academic year 2022/2023 and to find out students’ perception on the use of Duolingo application in improving their vocabulary mastery. In this research, the researcher takes mixed-method research: (a) quantitative: pre-experimental design with pre-test and post-test, and (b) qualitative: questionnaire. The researcher takes students in XI AP of SMK Gemilang Modernland as her subject of the research with four meetings. Based on the tests result, the students’ score is increased. The mean score of pre-test is 67.84, and the mean score of post-test is 77.52. It shows that the post- test’s mean is higher than the pre-test’s mean. Based on the questionnaire, the result of the research showed that the use of Duolingo in teaching English has many positive effects to the students, such as; the Duolingo feature was helpful to improving their motivation to study English, the characteristics of Duolingo can improve their effort in learning and Duolingo also make the students enjoy the exercises in learning English. Furthermore, nearly all students feel that they will continue to use Duolingo to study English.